COMPARING SCORING METHOD AND MODIFIED USDA METHOD TO DETERMINE LAND USE FUNCTION IN SPATIAL PLANNING - Wati, S. Eka; Sartohadi, J; Rossiter, D.G. (GEOMATIKA, 2010)
Land use function is basic information in spatial planning process. Land use function describes the area division based on its capability. Usually, land use function can be divided into three categories which are protected area, buffer area, and cultivated area. Recently, land use function in spatial plan document is generated by applying scoring method. However, land use function can be also obtained from land capability assessment published by USDA (United States Department of Agriculture). Land use function in this research is determined by using scoring method (regarding to legal document of Ministry of Agriculture number 837/Kpts/UM/11/1980 and number 683/Kpts/UM/8/1981) and proposed method (developed by modifying USDA land capability assessment). Land capability itself is assessed by using landform approach. Landform is obtained through interpretation of satellite image, topographic map, and field survey. Based on scoring method, the obtained range score is 90-195. The study area can be classified into protected zone (51%), buffer zone (31%), and cultivated zone (18%).On the other hand, proposed method gives some results that study area consists of five land capability classes, i.e. IV, V, VI, VII, and VIII. The percentage for each class is 26%, 2%, 2%, 12%, and 58% respectively. Related to land use function, this result represents that 58% of total area is allocated as protected zone, 16% of total area is classified as buffer zone, and the rest area is provided as cultivated zone.Key Words: Scoring method, USDA land capability classification, land use functionABSTRAKFungsi kawasan merupakan informasi dasar yang diperlukan proses dalam penyusunan rencana tata ruang. Fungsi kawasan menggambarkan pembagian area berdasarkan kemampuan yang dimilikinya. Pada umumnya, fungsi kawasan dibedakan menjadi tiga kategori, yaitu kawasan lindung, kawasan penyangga, dan kawasan budidaya/penanaman. Saat ini, fungsi kawasan dalam dokumen rencana tata ruang ditentukan dengan menggunakan metode skor. Meskipun demikian, fungsi kawasan dapat juga ditentukan dengan memanfaatkan perkiraan kemampuan lahan yang diterbitkan oleh USDA (United States Department of Agriculture). Fungsi kawasan pada penelitian ini ditentukan berdasarkan metode skor yang bersumber dari SK Menteri Pertanian No. 837/Kpts/UM/11/1980 dan No. 683/Kpts/UM/8/1981, sedangkan metode yang diusulkan dikembangkan dengan memodifikasi penilaian kemampuan lahan yang diterbitkan oleh USDA. Kemampuan lahan tersebut dinilai dengan menggunakan pendekatan bentanglahan. Bentang lahan diperoleh melalui interpretasi foto satelit, peta topografi dan survei lapangan. Berdasarkan metode skor, range skor yang didapatkan adalah 90 â 195. Wilayah studi dapat diklasifikasikan menjadi kawasan lindung (51%), kawasan penyangga (31%) dan kawasan budidaya (18%). Di sisi lain, metode yang diusulkan menghasilkan lima kelas kemampuan lahan yaitu kelas IV, V, VI, VII, dan VIII. Prosentase setiap kelas secara berurutan adalah 26%, 2%, 2%, 12%, and 58%. Berkaitan dengan fungsi penggunaan lahan, hasil ini menunjukkan bahwa 58% dari seluruh wilayah studi dialokasikan sebagai kawasan lindung, 16% dari total wilayah studi diklasifikasikan sebagai kawasan penyangga, sedangkan sisanya sebagai kawasan budidaya.Kata Kunci : Metode skor, klasifikasi kemampuan lahan USDA, fungsi kawasan